A novel calcium channel Cavβ2 splice variant with unique properties predominates in the retina - Seitter, Hartwig; Obkircher, Jana; Grabher, Patricia; Hartl, Julia; Zanetti, Lucia; Lux, Uwe; Fotakis, Georgios; Fernández-Quintero, Monica L.; Kaserer, Teresa; Koschak, Alexandra (Journal of Biological Chemistry, 2023)
Cavβ subunits are essential for surface expression of voltage-gated calcium channel complexes and crucially modulate biophysical properties like voltage-dependent inactivation. Here, we describe the discovery and characterization of a novel Cavβ2 variant with distinct features that predominates in the retina. We determined spliced exons in retinal transcripts of the Cacnb2 gene, coding for Cavβ2, by RNA-Seq data analysis and quantitative PCR. We cloned a novel Cavβ2 splice variant from mouse retina, which we are calling β2i, and investigated biophysical properties of calcium currents with this variant in a heterologous expression system as well as its intrinsic membrane interaction when expressed alone. Our data showed that β2i predominated in the retina with expression in photoreceptors and bipolar cells. Furthermore, we observed that the β2i N-terminus exhibited an extraordinary concentration of hydrophobic residues, a distinct feature not seen in canonical variants. The biophysical properties resembled known membrane-associated variants, and β2i exhibited both a strong membrane association and a propensity for clustering, which depended on hydrophobic residues in its N-terminus. We considered available Cavβ structure data to elucidate potential mechanisms underlying the observed characteristics but resolved N-terminus structures were lacking and thus, precluded clear conclusions. With this description of a novel N-terminus variant of Cavβ2, we expand the scope of functional variation through N-terminal splicing with a distinct form of membrane attachment. Further investigation of the molecular mechanisms underlying the features of β2i could provide new angles on the way Cavβ subunits modulate Ca2+ channels at the plasma membrane.
CRIS-Team Scopus Importer:2023-04-07
Keywords: alternative splicing; biophysics; calcium channel; photoreceptor; physiology; retina